Effects of phytocompound Precocene 1 on the expression and functionality of the P450 gene in λ-cyhalothrin-resistant Spodoptera litura (Fab.) - Shyam-Sundar, Narayanan; Ramasubramanian, Ramakrishnan; Karthi, Sengodan; Senthil-Nathan, Sengottayan; Chanthini, Kanagaraj Muthu-Pandian; Sivanesh, Haridoss; Stanley-Raja, Vethamonickam; Ramkumar, Govindaraju; Narayanan, Kilapavoor Raman; Mahboob, Shahid; Al-Ghanim, Khalid Abdullah; Abdel-Megeed, Ahmed; et al. (Frontiers in Physiology, 2022)
Spodoptera litura (Fabricius) is an agriculturally significant polyphagous insect pest that has evolved a high level of resistance to conventional insecticides. A dietary assay was used in this work to assess the resilience of field populations of S. litura to λ-cyhalothrin. Analysis of the function and expression of the cytochrome P450 gene was used to test the sensitivity of S. litura larvae to sub-lethal concentrations of the insecticidal plant chemical Precocene 1, both by itself and in combination with λ-cyhalothrin. The activity of esterase enzymes (α and β) was found to decrease 48 h post treatment with Precocene 1. The activity of GST enzyme and cytochrome P450 increased with Precocene 1 treatment post 48 h, however. Expression studies revealed the modulation by Precocene 1 of cytochrome P450 genes, CYP4M16, CYP4M15, CYP4S8V4, CYP4G31, and CYP4L10. While CYP4M16 expression was stimulated the most by the synergistic Precocene 1 + λ–cyhalothrin treatment, expression of CYP4G31 was the most down-regulated by Precocene 1 exposure. Hence, it is evident that λ–cyhalothrin-resistant pest populations are still sensitive to Precocene 1 at a sublethal concentration that is nevertheless capable of hindering their development. Precocene 1 can therefore be considered a potent candidate for the effective management of insecticide-resilient S. litura.